CLOUD COMPUTING - Kumar, Dr. Vinod; Raheja, Er. Gagandeep; Sodhi, Ms. Jyoti (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Cloud computing is the delivery of computing as a service rather than a product, whereby shared resources, software, and information are provided to computers and other devices as a utility (like the electricity grid) over a network (typically the internet). Cloud computing provides computation, software, data access, and storage services that do not require end-user knowledge of the physical location and configuration of the system that delivers the services. Parallel to this concept can be drawn with the electricity grid, wherein end-users consume power without needing to understand the component devices or infrastructure required to provide the service.